Deteksi Laju Deforestasi Pulau-Pulau Kecil Menggunakan Aplikasi Global Forest Change Studi Kasus: Kota Ternate Provinsi Maluku Utara - Sabaruddin B; Andy Kurniawan; Nurhikmah Nurhikmah (Program Studi Kehutanan Universitas Muslim Maros, 2023)
The rate of deforestation is a decrease or condition of losing the area of a forest area. This is caused by the activity of converting the status of forest areas into settlements, agriculture, plantations, etc. where these activities focus on improving the standard of living of the community. This study aims to detect the rate of deforestation on small islands in North Maluku, especially Ternate Island by using the Global Forest Change application. The research method uses a spatial approach to spatial analysis. This study shows that the rate of deforestation in the city of Ternate from 2001 to 2021 indicates that over a period of Â± 20 years there has been deforestation in the forest area of the city of Ternate. The area of the area is HPK, HL, HPHD and IUPHKM. The largest area of deforestation occurred in 2005 with an area of 8.9 ha, while the lowest occurred in 2021, namely 0.107 ha. Total total deforestation from 2001 â€“ 2021 which is 94.65 Ha. Keywords : Deforestation, Small islands, Spatial Analysis, Ternate, North Maluku